Intentional Suppression Can Lead to a Reduction of Memory Strength: Behavioral and Electrophysiological Findings - Waldhauser, Gerd T.; Lindgren, Magnus; Johansson, Mikael (Frontiers in Psychology, 2012)
Previous research has shown that the intentional suppression of unwanted memories can lead to forgetting in later memory tests. However, the mechanisms underlying this effect remain unclear. This study employed recognition memory testing and event-related potentials (ERPs) to investigate whether intentional suppression leads to the inhibition of memory representations at an item level. In a think/no-think experiment, participants were cued to either suppress (no-think condition) or retrieve (think condition) previously learned words, 18 or 0 times. Performance in a final recognition test was significantly reduced for repeatedly suppressed no-think items when compared to the baseline, zero-repetition condition. ERPs recorded during the suppression of no-think items were significantly more negative-going in a time window around 300 ms when compared to ERPs in the think condition. This reduction correlated with later recognition memory impairment. Furthermore, ERPs to no-think items from 225 to 450 ms were more negative-going in later phases of the experiment, suggesting a gradual reduction of memory strength with repeated suppression attempts. These effects were dissociable from correlates of recollection (500–600 ms) and inhibitory control (450–500 ms) that did not vary over the time-course of the experiment and appeared to be under strategic control. Our results give strong evidence that the no-think manipulation involves inhibition of memory representations at an item level.